2016
DOI: 10.1111/jfbc.12242
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Functional Components From Nelumbo Nucifera Root Fermented Broth with Antioxidant and Tyrosinase Inhibitory Effects

Abstract: The goals of this study were to develop a new functional beverage and/or syrup from Nelumbo nucifera (lotus) root by fermentation utilizing brown sugar and to determine its various functional properties and nutritive components. Total phenolic and flavonoid contents significantly increased after 15 and 30 days of fermentation as compared to control (brown sugar broth only) and their amounts ranged from 41–521 µg gallic acid equivalents/mL to 31–63 µg quercetin equivalents/mL, respectively. Gas chromatography‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Consequently, the syrup also showed a high anti‐oxidant activity, with an IC 50 of 87.25%, 99.52%, and 44.4% in DPPH, nitric oxide scavenging (NO), and superoxide radicals scavenging activity (SOD) assays, respectively. In addition, it was detected to have an anti‐tyrosinase activity of 49.8% (Shukla et al., ). The lotus leaf broth fermented over 180 d also showed good anti‐oxidant activity, comparable to ascorbic acid (Hwang, Charchoghlyan, Lee, & Kim, ).…”
Section: Health‐promoting Activitiesmentioning
confidence: 99%
“…Consequently, the syrup also showed a high anti‐oxidant activity, with an IC 50 of 87.25%, 99.52%, and 44.4% in DPPH, nitric oxide scavenging (NO), and superoxide radicals scavenging activity (SOD) assays, respectively. In addition, it was detected to have an anti‐tyrosinase activity of 49.8% (Shukla et al., ). The lotus leaf broth fermented over 180 d also showed good anti‐oxidant activity, comparable to ascorbic acid (Hwang, Charchoghlyan, Lee, & Kim, ).…”
Section: Health‐promoting Activitiesmentioning
confidence: 99%
“…In addition to this, the nutritional quality of lotus root fermented sugar syrup in aspects of amino acids, proteins and sugar contents revealed that the lotus root fermented sugar syrup provides a positive aspect for containing various nutritive components. In our earlier studies, we have reported that the lotus root fermented sugar syrup samples containing phenolic and flavonoid compounds exhibited remarkable antioxidant and tyrosinase inhibitory activities as compared to brown sugar broth (control) (Shukla et al 2016). The high scavenging properties of lotus root fermented sugar syrup samples might be due to phenolic compounds containing hydroxyl groups acting as radical scavengers.…”
Section: Sugar Contentmentioning
confidence: 96%